2011
DOI: 10.4025/actasciagron.v33i4.6387
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogênio em cobertura e molibdênio via foliar no feijoeiro irrigado cultivado em solo de cerrado

Abstract: RESUMO.O nitrogênio é o nutriente exigido em maior quantidade pelo feijoeiro e, mesmo quando suprida adequadamente desse nutriente, a planta de feijão pode ter sua produtividade limitada pela deficiência de molibdênio, pela participação deste no metabolismo do nitrogênio. O objetivo deste trabalho foi avaliar a resposta do feijoeiro (Phaseolus vulgaris L.), cultivar 'BRS Pontal', irrigado, à aplicação de nitrogênio em cobertura e molibdênio via foliar, quando cultivado em Neossolo Quartzarênico, no município d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 8 publications
0
10
1
7
Order By: Relevance
“…These results are the opposite of those reported by Biscaro et al (2012), who found a growth response up to the dose of 125 kg ha -1…”
Section: Growth Analysescontrasting
confidence: 57%
“…These results are the opposite of those reported by Biscaro et al (2012), who found a growth response up to the dose of 125 kg ha -1…”
Section: Growth Analysescontrasting
confidence: 57%
“…Calonego et al (2010) evaluated the effect of five N rates (25, 50, 75, 100 and 125 kg ha -1 ) applied 20 days after emergence (DAE) associated with and without foliar application of 80 g ha -1 Mo at 25 DAE and found that the molybdenum fertilization increased bean yield regardless of sidress N rates. In a similar study, Biscaro et al (2011) found that sidedress N increased the seed yield of common bean only when combined with foliar Mo.…”
Section: Mo Foliarmentioning
confidence: 83%
“…Although there is no response pattern to Mo, the increase in yield of the bean crop with supply of Mo has been reported in a number of studies in field conditions (Araújo et al, 2009;Nascimento et al, 2009;Biscaro et al, 2011;Rocha et al, 2011). Studies prove the feasibility of fertilizer foliar application on V4 stage bean, mainly of micronutrients tank-mixed with herbicides and pesticides to reduce costs and optimize equipment usage (Araújo et al, 2008;Silva et al, 2003b).…”
Section: Introductionmentioning
confidence: 96%
“…O feijão (Phaseolus vulgaris L.) é cultivado por pequenos, médios e grandes produtores utilizando os mais diversos tipos de sistemas em praticamente todas as regiões brasileiras (BISCARO et al, 2010 (TORRES et al, 2013). Para os brasileiros, o feijão é um constituinte básico da alimentação e o consumo por pessoa varia de acordo com a região, classe econômica e ainda pela preferência da cor dos grãos (ÁVILA et al, 2010).…”
Section: Introductionunclassified
“…O feijão (Phaseolus vulgaris L.) é cultivado por pequenos, médios e grandes produtores utilizando os mais diversos tipos de sistemas em praticamente todas as regiões brasileiras (BISCARO et al, 2010 (TORRES et al, 2013).…”
Section: Introductionunclassified